Factor VIII efficient and specific non-covalent binding to PEGylated liposomes enables prolongation of its circulation time and haemostatic efficacy - Baru, Moshe; Carmel-Goren, Lea; Barenholz, Yechezkel; Dayan, Inbal; Ostropolets, Savely; Slepoy, Igal; Gvirtzer, Nira; Fukson, Vladimir; Spira, Jack (Thrombosis and Haemostasis, 2005)
Haemophilia A is a bleeding disorder caused by the lack of factor VIII (FVIII). We report the prolongation of exogenous FVIII circulation time and haemostatic efficacy by its formulation with PEGylated liposomes (PEGLip). FVIII binds non-covalently but with high affinity in a specific mode with the external surface of PEGLip neither losing its activity nor its binding to von Willebrand Factor. Experiments in haemophilic and non-haemophilic mice indicate that the circulation time and clotting efficacy of PEGLip-formulated exogenous FVIII (PEGLip-FVIII) are significantly enhanced over those of free FVIII. The data support the feasibility of using PEGLip-FVIII to extend the duration of haemostatic efficacy in the treatment of haemophilia A.
Keywords: Factor VIII; haemophilia A; haemophilia therapy